Amore folle Based on a Novel by Maurice Renard - Renard, Maurice (Sinister Film, 2012)
Peter Lorre stars as Doctor Gogol, a man whose obsession with renowned theatre actress Yvonne Orlac ultimately turns to madness. When her husband Stephen's hands are badly crushed in a train accident, Yvonne asks Doctor Gogol to save the hands by any means possible. Gogol tells her that the hands are beyond repair; his solution is to graft the hands of executed murderer Rollo in place of Mr Orlac's useless ones. The operation goes as planned, however Orlac's new hands urge their unwitting owner to throttle people to death and kill them with supremely accurate knife throwing. When Gogol learns of Mr. Orlac's little problem, he delights upon convincing the hapless former pianist that he is losing his mind, toying with him with diabolical relish. Gogol ultimately sees this as his chance to finally win the love of Yvonne, but when she rejects his creepy advances he goes completely over the edge. A memorably unsettling Horror Thriller, "Mad Love" is a daring and disturbing look into the unsavoury realms of the perverse obsession and mentally unhinged behaviour which can lurk within certain individuals. [www.thecultmovieguide.com]